REVIEW OF READINESS FOR THE IMPLEMENTATION OF E-TICKETING AT NUSA PENIDA FERRY PORT, BALI PROVINCE - Kelana, Sri; Amrillah, Muhamad Fahmi; AN, Rizky (IWTJ : International Water Transport Journal, 2025)
The Nusa Penida Port is the only port on Nusa Penida Island that serves Ro-Ro vessels operating on the route to Padang Bai Port, Bali. Currently, the ticketing system is supported through an E-Ticketing platform via the Bali Santi website; however, ticket purchases are still predominantly carried out at the counter. This study aims to analyze passenger readiness for the implementation of E-Ticketing at Nusa Penida Port. The research method employs a descriptive quantitative approach with data collection techniques including observation, documentation, and passenger questionnaires. The findings indicate that although the E-Ticketing system is available, its utilization has not been optimal, as passengers continue to rely on manual services. Passenger readiness reached 69%, indicating a fairly good level of preparedness to support E-Ticketing implementation in accordance with the Minister of Transportation Regulation No. 19 of 2020. These findings emphasize the need for enhancing supporting facilities to ensure that E-Ticketing implementation can run effectively and provide convenience for port users.